2018
DOI: 10.1111/joa.12909
|View full text |Cite
|
Sign up to set email alerts
|

Cell viability in three ex vivo rat models of spinal cord injury

Abstract: Spinal cord injury (SCI) is a devastating disorder that has a poor prognosis of recovery. Animal models of SCI are useful to understand the pathophysiology of SCI and the potential use of therapeutic strategies for human SCI. Ex vivo models of central nervous system (CNS) trauma, particularly mechanical trauma, have become important tools to complement in vivo models of injury in order to reproduce the sequelae of human CNS injury. Ex vivo organotypic slice cultures (OSCs) provide a reliable model platform for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The levels of NT-3 measured at day 7 were lower than those observed at day 3 for slices transduced with NT-3 or with NT-3/NG2; however, they remained significantly higher than the control slices ( Figure 6). Previous studies in our group have shown that there is not a significant decrease in cell viability between day 3 and day 10 post-injury [53]. As lentiviral transduction leads to integration in the host Immunocytochemistry was performed to confirm the reduction in NG2 protein in Neu7 cells via measurement of total cell fluorescence intensity (Figure 4).…”
Section: Spinal Cord Slice Cultures Transduced With Nt-3 Lentiviral Vmentioning
confidence: 97%
See 1 more Smart Citation
“…The levels of NT-3 measured at day 7 were lower than those observed at day 3 for slices transduced with NT-3 or with NT-3/NG2; however, they remained significantly higher than the control slices ( Figure 6). Previous studies in our group have shown that there is not a significant decrease in cell viability between day 3 and day 10 post-injury [53]. As lentiviral transduction leads to integration in the host Immunocytochemistry was performed to confirm the reduction in NG2 protein in Neu7 cells via measurement of total cell fluorescence intensity (Figure 4).…”
Section: Spinal Cord Slice Cultures Transduced With Nt-3 Lentiviral Vmentioning
confidence: 97%
“…Each spinal cord was cut into pieces 1cm in length and transferred to sterile tissue chopper discs. Longitudinal sections of spinal cord were prepared and cultured as described previously [5,53]. In brief, spinal cord sections were cut to 350µm thickness on the McIIwain tissue chopper (Mickle Laboratory Engineering, Surrey, UK).…”
Section: Spinal Cord Transection and Lentiviral Vector Transductionmentioning
confidence: 99%
“…Historically, the SCI preclinical landscape has used in vitro, ex vivo, and in vivo models to unravel the complex multiphasic injury pathophysiology. [7][8][9] Lasting for up to 24 h, the "primary injury" phase is initiated by mechanical damage to the spinal cord and results in death of local neural and glial cells. [10,11] This triggers the "secondary injury" phase that propagates damage away from the primary injury site and lasts from weeks to months, and as a result is therapeutically targetable.…”
Section: Introductionmentioning
confidence: 99%